Enhanced binding of lymphocytes from patients with multiple sclerosis to tumour necrosis factor-alpha (TNF-α)-treated endothelial monolayers: associations with clinical relapse and adhesion molecule expression - VORA, A J (Blackwell Science Inc, 1996)
This study investigated the adherent properties and adhesion molecule expression of blood mononuclear cells (MNC) from a total of 84 patients with multiple sclerosis (MS). The MNC from MS patients were significantly more adherent than cells from normal healthy subjects to endothelial monolayers pretreated with 0.01 U/ml TNF-α (103% increase; P = 0.002), 0.1 U/ml TNF-α (80% increase; P< 0.01) and 1.0 U/ml TNF-α (41% increase; P< 0.02), and to endothelium pretreated with 10 U/ml IL-1β (44% increase; P< 0.05) and 100 U/ml interferon-gamma (IFN-γ) (100% increase; P< 0.05). This augmented adhesion was a property of the lymphocytes, in particular CD4(+) cells, and was inversely related to the time of onset of clinical relapse. The percentage of lymphocytes bearing the adhesion molecules CD49d, CD29 and CD62L was increased in MS blood, but the level of CD29 and CD62L expression was reduced. We infer that circulating lymphocytes in MS are predisposed to cross endothelial barriers at sites where inflammation has already commenced.